Accuracy improvement in 3D laser scanner based on dynamic triangulation for autonomous navigation system - Real-Moreno, Oscar; Rodríguez Quiñonez, Julio C.; Sergiyenko, Oleg; Básaca-Preciado, Luis C.; Hernández-Balbuena, Daniel; Rivas-Lopez, Moisés; Flores-Fuentes, Wendy (My University, 2017)
Autonomous navigation has been an important task in recent years to keep track of vehicles location, to provide safety and accuracy on its trajectory and to see their surroundings and predict if it is possible to travel across them. In this paper, a method to improve accuracy on laser vision systems based on dynamic triangulation for mobile robots is proposed. This laser vision system consists on a positioning laser, a scanning aperture and a fixed distance between them. The positioning laser points a laser beam over a surface and it is detected by the scanning aperture. The proposed method to improve accuracy on laser vision systems relies on the scanning aperture; current designs calculate the detection angle counting the pulses of a pulse train across a motor rotation. The disadvantage of this method is that the angular velocity of the motor may vary, resulting in an incorrect calculation of the angle of detection. In the proposed method, a new signal provided by an encoder is used to reduce the error generated by variations in angular velocity.
IEEE International Symposium on Industrial Electronics
Keywords: Laser; Scanner; Triangulation; Scanning aperture; Autonomous navigation